HISTOPATHOLOGICAL PATTERNS OF LESIONS CAUSED BY TWO DICHORHAVIRUS - Marques, João Paulo Rodrigues; Tassi, Aline Daniele; Filippi, Gustavo Mortean; Salaroli, Renato; Kitajima, Elliot Watanabe (REVISTA DE AGRICULTURA, 2020)
Different from most plant viruses, Brevipalpus mite-transmitted viruses (BTV) cause localized infection, not being able to systemically invade the infected plant. To broaden the specter of the histopathological changes in leaf tissues induced by BTV infection, we examined the tissue organization of leaf lesions caused by the infection of two additional representatives of dichorhaviruses, Clerodendrum chlorotic spot virus (ClCSV) and Coffee ringspot virus (CoRSV). In general, tissue alterations within the lesions followed the pattern noticed in CiLV-C and CiLV-N infection. In all analyzed lesions, necrotic cells form the central region that is surrounded by a chlorotic halo where hypertrophied cells commonly occur. Presence of reactive oxygen components were also a characteristic of the chlorotic halo. Though more cases of localized lesions on leaves infected by more BTV, remains to be analyzed, it seems that these lesions respond similarly upon infection by BTV, either Cile- or Dichorhavirus.